2011
DOI: 10.1136/bcr.09.2011.4755
|View full text |Cite
|
Sign up to set email alerts
|

Rowell syndrome - case report with discussion of significance of diagnostic accuracy

Abstract: Rowell syndrome is a very controversial condition and though defining diagnosing criteria exist, many previously published cases lack one or more of these criteria. It represents the combination of cutaneous lupus erythematosus and erythema multiforme in one single individual. In order to discuss relevance of diagnostic and defining criteria the authors use a case seen in our outpatient service that was primarily diagnosed as Rowell syndrome. But due to lacking criteria, the authors rediagnosed this patient as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Histologically, this condition is characterized by apoptotic keratinocytes or significant epidermal necrosis such as in EM, interface dermatitis, and a superficial and deep perivascular lymphocytic infiltrate with variable interstitial mucinosis as in LE [8,9].…”
Section: Case Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histologically, this condition is characterized by apoptotic keratinocytes or significant epidermal necrosis such as in EM, interface dermatitis, and a superficial and deep perivascular lymphocytic infiltrate with variable interstitial mucinosis as in LE [8,9].…”
Section: Case Discussionmentioning
confidence: 99%
“…No standard treatment exists for Rowell syndrome. Drugs including but not limited to systemic and topical steroids, anti-malarials such as hydroxychloroquine and chloroquine, and immunosuppressive agents such as methotrexate, azathioprine, cyclosporine, and dapsone have been used with variable success [3,8].…”
Section: Case Discussionmentioning
confidence: 99%
“…Pregnancy may have precipitated the emergence of cutaneous lesions in our patient. Successful results have been observed with immunosuppressive drugs such as corticosteroids, HCQ, azathioprine, dapsone, mycophenolate mofetil, and cyclosporine in the literature 3 8 9 . Our patient’s skin lesions disappeared leaving hyperpigmentation after cyclosporine was added to her current treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Most reports show a successful treatment using systemic steroids and additional immunosuppressive drugs such as azathioprine and cyclosporine. Some studies also reported the use of topical steroids in the management of RS with variable response [ 8 , 9 ]. Zeitouni et al also described a case of RS that responded to treatment with dapsone [ 3 ].…”
Section: Discussionmentioning
confidence: 99%